2015
DOI: 10.1063/1.4922460
|View full text |Cite
|
Sign up to set email alerts
|

Negative linear compressibility in common materials

Abstract: Negative linear compressibility (NLC) is still considered an exotic property, only observed in a few obscure crystals. The vast majority of materials compress axially in all directions when loaded in hydrostatic compression. However, a few materials have been observed which expand in one or two directions under hydrostatic compression. At present, the list of materials demonstrating this unusual behaviour is confined to a small number of relatively rare crystal phases, biological materials, and designed struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…The magnitude of NLC can be compared by means of isothermal compressibilities K NLC = (∂lnl/∂p) T , defined in terms of the relative rate of change of length ‘l’ with respect to pressure. Further on our calculations demonstrate this material exhibits strong NLC with the magnitude K NLC = −7.9(5) TPa −1 which is almost twice as much as values reported for the majority of materials with NLC 1 2 3 . Abnormal compressibility of NaAB is quite unexpected as its crystal structure reveal no characteristic feature, e.g., tilting/rotating polyhedra networks, helices, specific framework topologies – typically shared by known materials with NLC.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The magnitude of NLC can be compared by means of isothermal compressibilities K NLC = (∂lnl/∂p) T , defined in terms of the relative rate of change of length ‘l’ with respect to pressure. Further on our calculations demonstrate this material exhibits strong NLC with the magnitude K NLC = −7.9(5) TPa −1 which is almost twice as much as values reported for the majority of materials with NLC 1 2 3 . Abnormal compressibility of NaAB is quite unexpected as its crystal structure reveal no characteristic feature, e.g., tilting/rotating polyhedra networks, helices, specific framework topologies – typically shared by known materials with NLC.…”
Section: Resultssupporting
confidence: 65%
“…Despite the counterintuitive character the phenomenon does not violate basic thermodynamic principle of overall volume reduction under pressure and may lay foundation for development of effectively incompressible materials for various practical applications, including materials for artificial muscles, amplification of piezoelectric response in sensors and actuators, tunable sieves for filtration, “smart” body armor made of robust shock absorbing materials, sensitive pressure detectors, materials used at deep sea, etc. The most significant challenges in this field have been the apparent rarity of materials showing NLC, the extreme weakness of the NLC effect found in these materials and little understanding of mechanisms governing NLC in particular materials 1 2 3 . Examples of NLC were reported in extensive inorganic (or organic), metal-organic as well as molecular framework materials 4 5 6 7 .…”
mentioning
confidence: 99%
“…0 the cell volume at ambient pressure, B 0 and C 0 are the isothermal bulk modulus and its derivative against pressure at p = 0, respectively. Contrary to what reported for phases I26,27 and III,26 a positive linear compressibility in all the crystallographic directions is here observed for phase IV.The coincidence of phases II and IV was further investigated by single crystal experiments. The P-T region indicated by Bridgman as pertaining to phase II was reached by two different P-T paths.…”
contrasting
confidence: 90%
“…Recently, Cairns and Goodwin reviewed the phenomenology of negative compressibility in multifarious materials and presented a mechanistic understanding of negative compressibility. Miller et al identified several relatively common materials which displayed NLC and presented several potential applications.…”
Section: Introductionmentioning
confidence: 99%